Pollution, Infectious Disease, and Mortality: Evidence from the 1918 Spanish Influenza Pandemic - Karen Clay; Joshua Lewis; Edson R. Severnini (Institute for the Study of Labor (IZA), 2015)
This paper uses the 1918 influenza pandemic as a natural experiment to examine whether air pollution affects susceptibility to infectious disease. The empirical analysis combines the sharp timing of the pandemic with large cross-city differences in baseline pollution measures based on coal-fired electricity generating capacity for a sample 183 American cities. The findings suggest that air pollution exacerbated the impact of the pandemic. Proximity to World War I military bases and baseline city health conditions also contributed to pandemic severity. The effects of air pollution are quantitatively important. Had coal-fired capacity in above-median cities been reduced to the median level, 3,400-5,860 pandemic-related infant deaths and 15,575-23,686 pandemic-related all-age deaths would have been averted. These results highlight the complementarity between air pollution and infectious disease on health, and suggest that there may be large co-benefits associated with pollution abatement policies.
Keywords: N32; N52; I15; I18; Q53; Q56; Q58; 330; pollution; infectious disease; mortality; 1918 influenza pandemic